The rice diet renewal : a healing 30-day program for lasting weight loss - Rosati, Kitty Gurkin, 1954- (Hoboken, N.J. : Wiley, 2010)
'The Rice Diet Renewal' goes beyond what you eat to help you heal the roots of the emotional, mental, and spiritual underpinnings that often get in the way of achieving and maintaining weight loss
Includes bibliographical references and index
Keywords: Reducing diets; High-carbohydrate diet